Sensitive Reading The Pleasures of South Asian Literature in Translation - Bronner, Yigal; Hallisey, Charles (University of California Press, 2022)
What are the pleasures of reading translations of South Asian literature, and what does it take to enjoy a translated text? This volume provides opportunities to explore such questions by bringing together a whole set of new translations by David Shulman, noted scholar of South Asia. The translated selections come from a variety of Indian languages, genres, and periods, from the classical to the contemporary. The translations are accompanied by short essays written to help readers engage and enjoy them. Some of these essays provide background to enhance reading of the translation, whereas others model how to expand appreciation in comparative and broader ways. Together, the translations and the accompanying essays form an essential guide for people interested in literature and art from South Asia. "The scholarly interpretations and commentary in this volume represent some of the most prominent voices in the philological and historical study of South Asia-a galaxy of experts in literary analysis and other subfields of South Asian cultural history. This volume beautifully illuminates the generative possibilities of the intimate, context-sensitive mode of reading that David Shulman has engaged in for decades." DAVESH SONEJI, Department of South Asia Studies, University of Pennsylvania